Oribatid mites (Acari, Oribatida) of bushy patches in steppe vegetation of cape Tarkhankut in Crimea (Ukraine) - Seniczak, Stanisław; Kaczmarek, Sławomir; Seniczak, Anna (Biological Letters, 2012)
The density, species number, and age structure of oribatid mites were investigated in bushy patches (elm, hawthorn, hawthorn with rose) in steppe vegetation of cape Tarkhankut (Crimea). In these patches, the density of mites in shrub litter, herbs and moss was higher, but species number was similar like in open steppe vegetation. Hawthorn increased the density distinctly more than hawthorn with rose or bushy elms. In bushy patches, the samples of moss were richer in mites than samples of shrub litter alone or with herbs. Among oribatid mites, Chamobates c.f. spinosus and Trhypochthonius tectorum were most abundant, but relatively abundant and common were also Tectocepheus velatus, Oribatula sp. 1, Achipteria nitens, and Brachychthonius berlesei. In oribatid mite communities, adults dominated, but the age structure of populations greatly depended on vegetation type.